OAK WOOD AND BARK CONTAMINATION WITH 137CS IN HIGH-AGE STANDS IN THE EXCLUSION ZONE OF THE CHERNOBYL NUCLEAR POWER PLANT - Гарбарук, Дмитрий; Uglyanets, Anatoliy (Journal of the Belarusian State University. Ecology, 2024)
The results of studying the 137Cs contamination of oak trunks in high-aged oak forests in the near zone of the Chernobyl nuclear power plant are presented. The features of surface contamination soil by 137Cs in them are revealed. The indicators of its accumulation in wood, bark and unbarked oak trunks by forest types and their correlation relationship with the density of soil contamination and the distance to the disaster site are determined. A 2–3-fold excess of bark contamination was found in comparison with wood. The relative contribution of each of these components to the specific activity of 137Cs in the trunks is calculated. The distribution of radionuclide in oak wood by classes of growth and development of trees and in dead wood is shown. The tendency of decreasing of 137Cs concentration in its wood from the periphery to the center of the trunk has been confirmed. As of 2021, according to the sanitary standard of the Republic of Belarus for the content of 137Cs 1480 Bq kg–1, harvesting of oak debarked wood was permissible in 84% of the surveyed stands, unbarked wood – in 72%. Debarked and unbarked wood corresponded to the standard of 740 Bq kg–1 in 32% of stands.
Keywords: Chernobyl Nuclear Power Plant; exclusion zone; oak; wood; bark; 137Cs; specific activity; transition coefficient